Improvement of internal target designation system for modern and advanced armored weapons samples - V. I. Kirnos; A. V. Zubar’; E. A. Geyntse (Омский научный вестник)
The article presents a brief analysis of the existing methods of internal target designation used on existing models of armored weapons. The authors propose the method of internal target designation and target indication based on the mathematical description of interrelation between coordinates of the image of an object in the visual field of a sight and its three-dimensional coordinates in world coordinate system.